PENDIDIKAN NONFORMAL DAN PENGURANGAN KEMISKINAN DI PEDESAAN - Tohani, Entoh (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
Non-formal education through life skills education has shown a positive contribution to poverty reduction in rural development efforts, although still requiring efforts to life skills education development. The research was conducted in Kulonprogo, and the District of Gunungkidul, with research and development approach on life skills education programs are being implemented in two districts e.i KWK Rabbits Livestock in Gunungkidul and KWD Hair Dressers in Kulonprogo. The results showed that: life skills education needs assessment in the two target groups were performed using the idea of life skills 4-H shows are not much different conditions, and based on the needs of the development, 4-H life skills education model developed with a focus on experience-based learning. Development of validated models show the results (output) is positive. Therefore, in the context of poverty reduction in 4-H PKH models should be developed more structured and integrative and guarantee all the life skills that are the focus of life skills development efforts to overcome poverty.***Pendidikan non-formal melalui pendidikan ketrampilan telah menunjukkan kontribusi positif terhadap penurunan angka kemiskinan dalam pembangunan pedesaaan. Penelitian ini dilaksanakan di Kulonprogo dan Gunung Kidul dengan pendekatan penelitian dan pengembangan yang diimplementasikan di kelompok peternakan kelinci di Gunungkidul dan di kelompok perawatan rambut di Kulonprogo. Hasilnya menunjukkan bahwa: estimasi kebutuhan pendidikan ketrampilan di dua kelompok target yang dilaksanakan dengan menggunakan ide tentang life skill 4-H menunjukkan kondisi yang tidak jauh berbeda, model life skill 4-H dikembangkan dengan fokus pembelajaran berbasis pengalaman. Pengembangan model validasi memberikan hasil positif. Oleh karena itu dalam konteks penurunan angka kemiskinan dalam model PKH 4-H harus dikembangkan secara lebih terstruktur dan integratif serta menjamin semua pendidikan ketrampilan berorientasi pada penanganan kemiskinan.